2022
DOI: 10.3390/biomedicines10102646
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Pulmonary Co-Infections on ICU Admission: Comparison in Patients with SARS-CoV-2 and Influenza Acute Respiratory Failure: A Multicentre Cohort Study

Abstract: Background: Few data are available on the impact of bacterial pulmonary co-infection (RespCoBact) during COVID-19 (CovRespCoBact). The aim of this study was to compare the prognosis of patients admitted to an ICU for influenza pneumonia and for SARS-CoV-2 pneumonia with and without RespCoBact. Methods: This was a multicentre (n = 11) observational study using the Outcomerea© database. Since 2008, all patients admitted with influenza pneumonia or SARS-CoV-2 pneumonia and discharged before 30 June 2021 were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In a multicenter study including 1349 patients, Delhommeau et al [ 36 ] found significantly higher mortality at day 60 in patients with CP compared to IP. In accordance with our data, the mortality risk did not increase due to c/s.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter study including 1349 patients, Delhommeau et al [ 36 ] found significantly higher mortality at day 60 in patients with CP compared to IP. In accordance with our data, the mortality risk did not increase due to c/s.…”
Section: Discussionmentioning
confidence: 99%
“…Most of our data came from retrospective research, and there might have been selection bias. Of the 35 articles we included, only 5 articles 15,19,26,33,34 clearly noted that there was no cross-infection between the two types of patients, and other articles did not elaborate on this. Vaccination has a great influence on the severity and prognosis of COVID-19 patients and influenza patients, but unfortunately, none of the studies we included described the vaccination status of patients in detail.…”
Section: Limitationsmentioning
confidence: 99%
“…Although this is a well-established definition used in the literature, differentiating between bacterial coinfection and colonialization is not always possible. Nonetheless, both bacterial coinfections and colonialization at time of intubation have been shown to be associated with a higher mortality depending on the documented pathogen and the number of comorbidities [11]. In regard to VAP, we counted bacterial superinfection more than 48 h after intubation as VAP according to the literature [17,18].…”
Section: Microbiological Screeningmentioning
confidence: 99%
“…Previous studies investigated the prevalence of coinfection of SARS-CoV-2 patients and influenza patients upon hospital admission. Delhommeau et al showed that bacterial coinfection in SARS-CoV-2 patients was less frequent than in patients with influenza (8.2% for SARS-CoV-2 versus 24.8% for influenza) [11]. Furthermore, the prevalence of coinfection was not associated with a higher mortality or with the development of VAP [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation